The Relationship between Problem-Solving Skills and Memory Development in Preschool Children - Aydoğan, Yasemin; Özyürek, Arzu (Journal of History Culture and Art Research, 2020)
The present study aimed to investigate the correlation between problem-solving and memory skills in preschool children. The study group included 122 4-6 years olf children attending pre-school education institutions. Random sampling method was used to determine the study participants. Data were collected with Problem-Solving Skills Scale (PSSS) and Memory Scale for Children (MSC). In data analysis, Pearson’s correlation coefficient was used to determine the correlation between the scale scores. The t test and one-way analysis of variance (ANOVA) were used to determine the effect of gender of the children, parental age and educational status on problem solving and memory. The study findings demonstrated that there was a significant correlation between the PSSS and MSC subscale scores, and the problem-solving skills and memories of pre-school children were not affected by gender, school type, parental age and profession, and mother’s educational status. There was a difference between memory scores of the children based on the father’s educational status and no significant difference was determined in problem-solving skills.